2022
DOI: 10.3390/cancers14174268
|View full text |Cite
|
Sign up to set email alerts
|

What Is the Current Role and What Are the Prospects of the Robotic Approach in Liver Surgery?

Abstract: In parallel with the historical development of minimally invasive surgery, the laparoscopic and robotic approaches are now frequently utilized to perform major abdominal surgical procedures. Nevertheless, the role of the robotic approach in liver surgery is still controversial, and a standardized, safe technique has not been defined yet. This review aims to summarize the currently available evidence and prospects of robotic liver surgery. Minimally invasive liver surgery has been extensively associated with be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 107 publications
(116 reference statements)
1
11
0
Order By: Relevance
“…These findings are also in line with the expectation that the enhanced dexterity and superior visual capabilities of the robotic approach could mainly be beneficial during more complex resections. 15,38 In spite of the ongoing debate on its advantages and disadvantages, the Pringle maneuver has been increasingly employed in recent decades to reduce blood loss during parenchymal transection and thus facilitate a dry surgical field. 39,40 In our analysis, we consistently found lower Pringle usage and shorter duration in the RLS group, which is in line with earlier reports.…”
Section: A C C E P T E Dmentioning
confidence: 99%
See 2 more Smart Citations
“…These findings are also in line with the expectation that the enhanced dexterity and superior visual capabilities of the robotic approach could mainly be beneficial during more complex resections. 15,38 In spite of the ongoing debate on its advantages and disadvantages, the Pringle maneuver has been increasingly employed in recent decades to reduce blood loss during parenchymal transection and thus facilitate a dry surgical field. 39,40 In our analysis, we consistently found lower Pringle usage and shorter duration in the RLS group, which is in line with earlier reports.…”
Section: A C C E P T E Dmentioning
confidence: 99%
“…13,46 Currently however, the properties of the robot seem to offer certain benefits in this regard, which allow surgeons to complete more procedures in a minimally invasive fashion. 15 Some authors have suggested that the decrease in conversion rates is related to the fact that there is less need to convert to achieve oncological radicality and control bleeding in RLS. 16,43 The exact reason for this difference however remains unclear, warranting additional studies focusing on this topic.…”
Section: A C C E P T E Dmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent review by Bozkurt et al. summarized the current evidence regarding robotic liver surgery [ 10 ]. The widely proven advantages of minimally invasive liver surgery are less intraoperative blood loss, less postoperative pain, and shorter hospital stay than open liver surgery.…”
Section: Minimally Invasive Liver Surgerymentioning
confidence: 99%
“…Hepatectomy is increasingly performed via a robotic approach, like other gastrointestinal surgeries [1][2][3][4]. In open or laparoscopic liver resection, various optimized devices for parenchymal dissection (e.g., ultrasonic aspirator [5,6] and ultrasonic incision coagulator [7,8]) are available.…”
Section: Introductionmentioning
confidence: 99%